2023
DOI: 10.3390/polym15193937
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobized MFC as Reinforcing Additive in Industrial Silica/SBR Tire Tread Compound

Ming Liu,
Iikpoemugh Elo Imiete,
Mariapaola Staropoli
et al.

Abstract: Silica is used as reinforcing filler in the tire industry. Owing to the intensive process of silica production and its high density, substitution with lightweight bio-based micro fibrillated cellulose (MFC) is expected to provide lightweight, sustainable, and highly reinforced tire composite. MFC was modified with oleoyl chloride, and the degree of substitution (DS) was maintained between 0.2 and 0.9. Subsequently, the morphology and crystallinity of the modified MFC were studied and found to be significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Fasolt et al [ 14 ] found that electrodes impact the breakdown voltage in dielectric elastomer actuators, which can be improved using stiffer, silicone rubber-based electrodes. Furthermore, Liu et al [ 15 ] used hydrophobized, bio-based, microfibrillated cellulose as a reinforcing filler in silica/styrene butadiene rubber (SBR) tire tread compounds, observing a notable increase in mechanical properties compared to the sole use of silica/SBR compounds. Meanwhile, Wang et al [ 16 ] enhanced the mechanical, dielectric, and hydrophobic properties of commonly used Methyl Vinyl Silicone Rubber by blending it with Fluorosilicone Rubber.…”
Section: Overview Of Published Articlesmentioning
confidence: 99%
“…Fasolt et al [ 14 ] found that electrodes impact the breakdown voltage in dielectric elastomer actuators, which can be improved using stiffer, silicone rubber-based electrodes. Furthermore, Liu et al [ 15 ] used hydrophobized, bio-based, microfibrillated cellulose as a reinforcing filler in silica/styrene butadiene rubber (SBR) tire tread compounds, observing a notable increase in mechanical properties compared to the sole use of silica/SBR compounds. Meanwhile, Wang et al [ 16 ] enhanced the mechanical, dielectric, and hydrophobic properties of commonly used Methyl Vinyl Silicone Rubber by blending it with Fluorosilicone Rubber.…”
Section: Overview Of Published Articlesmentioning
confidence: 99%
“…High‐performance tires, which are crucial for the operation and advancement of modern industry and society, are a strategic material with a vital role in various applications 3,4 . In recent years, silica has increasingly replaced carbon black as the primary filler for high‐performance tires, resulting in improved anti‐skid performance and reduced rolling resistance of the tires 5–8 . However, the presence of a substantial number of polar silica hydroxyl groups on the surface of the silica leads to strong filler–filler interactions through hydrogen bonding between silanol groups, causing easy agglomeration 9–12 .…”
Section: Introductionmentioning
confidence: 99%
“…3,4 In recent years, silica has increasingly replaced carbon black as the primary filler for highperformance tires, resulting in improved anti-skid performance and reduced rolling resistance of the tires. [5][6][7][8] However, the presence of a substantial number of polar silica hydroxyl groups on the surface of the silica leads to…”
mentioning
confidence: 99%